Interview (2010)
Interview with Sarah Ochoa, participant of Expeditions to Knowledge, especifically Expedition to Art in the City: “The expedition to Art in the City is an artistic intervention. We are breaking the routine, because supposedly the university is only aplace to study and there is not a minute left. We are getting in the way, drawing attention, so that people stop and have the opportunity to sit, rest and play; things they haven't done since they entered college.